Fatty Acid Profile of Fresh and Smoked Indian Scad (Decapterus russelli) - Cindy Regina Magdalena Loppies; Dwight Soukotta; Beni Setha; Eirene Tentua (Jurnal Perikanan Universitas Gadjah Mada, 2022)
Fishery products are a high source of nutrients, especially fatty acids. The smoking technology with liquid smoke is being developed to preserve fishery products. With this processing, fish are expected to be more durable and have better nutritional content, especially polyunsaturated fatty acids (PUFA), needed in the body. For this reason, research has been carried out to see the impact of fish processing with liquid smoke technology on the fatty acid profile of smoked Indian scad. The method used is the experimental method using coconut shell liquid smoke and samples of fresh and smoked Indian scad. The results showed that the fatty acid profile of fresh and smoked Indian scad contained 27 types of fatty acids consisting of 11 saturated fatty acids and 16 unsaturated fatty acids. The content of polyunsaturated fatty acids (PUFA) in fresh and smoked Indian scad is greater than the content of saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA). The high ratio of PUFA-ω3/PUFA-ω6 and the low value of Index of Atherogenic (IA) and Index of Thrombogenic (IT) of fresh and smoked Indian scad treated with coconut shell liquid smoke indicate the quality of fish fat is very good for consumption which is beneficial for health.